The interview: methodological framework in the study of "Tourism and economics: the Faro airport (1946-73)" - Pereira, Renato Nuno (2013)
This methodological paper defines how to interview people regarding the decision-making process, construction and operation of Faro Airport and its role in the Portuguese tourism policy for the Algarve between 1946 and 1973. The interviewee’s age makes these interviews urgent and unique. We will hear retired workers and people who held head positions at the airport or in other relevant public or private organizations. The interviews will allow the access to data otherwise not attainable or not sufficiently evident in other sources, such as documents. The interview consists of hearing the stories of the people, as a narrative, being the interview a semi-structured, guided and unstructured mix. The use of photographs during the interview will help respondents recall events that occurred decades ago. The interviewee will be selected by snowball sampling technique. Content analysis is the method to obtain data from the transcripts of the interviews, in order to construct a coherent narrative and with the contribution of all the interviews and interviewee. As field instruments, we will use an informed consent form, photographs and the confidentiality form after the interview, which responds to the ethical requirement for confidentiality, consequences of the interview and the role of the researcher.